2024
DOI: 10.30892/gtg.52125-1202
|View full text |Cite
|
Sign up to set email alerts
|

Tourist Satisfaction and Revisit Intention: The Role of Attraction, Accessibility, and Facilities of Water Park Tourism

Aceng Gima SUGIAMA,
Dwi SUHARTANTO,
Carol Yirong LU
et al.

Abstract: Although it is crucial to investigate the effect of tourism components on satisfaction and revisit intention, there has not been any similar study that specifically explores the perception of young tourists visiting water parks. This study aims to investigate the effect of attraction, accessibility, and facilities on satisfaction and revisit intention. Using quantitative research methods with 269 young water park tourists, the data were analyzed by using SEM-PLS modeling. The results reveal that attraction, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Indeed, tangible factors contribute positively to the quality service experience of tourists (Hai et al, 2023). The finding is consistent with studies proposed by Ibrahim et al (2015), Shah et al (2018), Long (2019), Masrurul (2019), Thuy (2020), Hong et al (2022), Cheraghzadeh et al (2023, Sapkota et al (2023), andSugiama et al (2024).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, tangible factors contribute positively to the quality service experience of tourists (Hai et al, 2023). The finding is consistent with studies proposed by Ibrahim et al (2015), Shah et al (2018), Long (2019), Masrurul (2019), Thuy (2020), Hong et al (2022), Cheraghzadeh et al (2023, Sapkota et al (2023), andSugiama et al (2024).…”
Section: Discussionsupporting
confidence: 88%
“…Talukder et al (2024) established a positive relationship between the quality of ecological services (reliability, responsiveness, assurance, empathy, tangibles) and tourist satisfaction with Kuakata destination in Bangladesh. Sugiama et al (2024) identified that attractiveness, accessibility, and facilities are significant predictors of satisfaction and intention to revisit water parks among young tourists.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation